State of peril race and rape in South African literature - Graham, Lucy Valerie, 1973- (New York ; Oxford : Oxford University Press, 2012)
This title surveys the troubling theme of rape and racism in South African literature by examining works by Zoe Wicomb, J.M. Coetzee, Nadine Gordimer, and others.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Keywords: South African literature (English) -- History and criticism; Rape in literature; Race relations in literature